Green Environment, Mental Health, and Loyalty among Male and Female Patients - Elena-Nicoleta Untaru; Antonio Ariza-Montes; Hyeran Kim; Heesup Han (Journal of Men's Health, 2022)
Background: Existing studies revealed that exposure to green spaces within healthcare establishments has multiple physical and mental health benefits to patients. In this context, the concept of biophilic design has received growing attention among environmental psychology researchers. Several studies indicated that the positive effect of green environment may be different for males and females. Therefore, the present study sought to investigate the influence of biophilic design elements (i.e., green items and natural light) on patients’self-rated mental health value, satisfaction with medical care, and loyalty toward the healthcare establishment. The study also investigated the possible influence of gender differences in the relationships between the variables. Methods: A structural equation modeling was employed as a data analysis technique. Results: Our empirical result indicated that biophilic design elements significantly improved the patients’ self-rated mental health value, and this dimension had a positive effect on their satisfaction with medical care and loyalty toward the health care facility. Our findings indicated that the relationships among biophilic design elements, self-rated mental health value, satisfaction with medical care, and loyalty toward the healthcare establishment were substantially different across male and female groups. Moreover, self-rated mental health value and satisfaction with medical care acted as significant mediators between biophilic design elements and loyalty. Conclusions: Results of this study offer healthcare practitioners and researchers valuable strategies to effectively incorporate biophilic design elements into the interior spaces of a healthcare establishment.